Characteristics and drivers of plant C, N, and P stoichiometry in Northern Tibetan Plateau grassland - Wang, Wei; Zhao, Jiamin; Xing, Zhen; Wang, Xiangtao (Frontiers in Plant Science, 2023)
Understanding vegetation C, N, and P stoichiometry not only helps us to evaluate biogeochemical cycles and ecosystem functions but also to predict the potential impact of environmental change on ecosystem processes. The foliar C, N, and P stoichiometry in northern Tibetan grasslands, especially the controlling factors, has been highlighted in recent years. In this study, we examined the foliar C, N, and P stoichiometry and underlying control factors in three grassland types along a 1500-km east-to-west transect in the Northern Tibetan Plateau. Our results indicated that foliar C, N, and P concentrations were 425.9±15.8, 403. 4±22.2, and 420.7±30.7 g kg-1; 21.7±2.9, 19.0±2.3, and 21.7±5.2 g kg-1; and 1.71±0.29, 1.19±0.16, and 1.59±0.6 g kg-1 in alpine meadow (AM), alpine steppe (AS), and desert steppe (DS) ecosystems, respectively. The foliar C and N ratios were comparable, with values of 19.8±2.8, 20.6±1.9, and 19.9±5.8 in the AM, AS, and DS ecosystems, respectively. Both the C/P and N/P ratios are the lowest in the AM ecosystem, with values of 252.2±32.6 and 12.8±1.3, respectively, whereas the highest values of 347.3±57.0 and 16.2±3.2 were obtained in the AS ecosystem. In contrast, the soil C, N, C/P, and N/P values decreased from AM to DS ecosystems. Across the whole transects, leaf C, N, and P stoichiometry showed no obvious trend, but soil C and N concentrations showed an increasing trend, and soil P concentrations showed a decreasing trend with the increasing of longitude.in addition, the vegetation type was the dominant factor controlling the leaf C, N, and P stoichiometry, the soil nutrients and climate has a relatively low importance. In conclusion, our results supported that between-species variation, rather than climatic variation and soil nutrient, are the major determinants of north Tibet grassland leaf stoichiometry.